Karşılaştırmalı hukukta temsil - Karasu, Bülent (My University, 2018)
Günümüzde sözleşmelerin kuruluşunda yer alan taraflar ile sınırlı olarak hüküm doğurması anlayışı köklü değişikliklere uğramıştır. İşlem hayatının gösterdiği hızlı değişim, temsil kurumunu zorunlu bir olgu haline getirmiştir. Bu doğrultuda temsil kurumu başta ulusal hukuk sistemlerinde olmak üzere birçok uluslararası hukuk belgesinde önemli düzenlemelere konu olmuştur. Hukuk sistemimizde öngörülen temsile ilişkin hükümlerin belirsizliği ve tarafların menfaatlerini dengeli bir şekilde korumaması, bu konudaki kuralların yeniden değerlendirilmesi ihtiyacını doğurmuştur. Çalışmamızda uyumlaştırma faaliyetleri ışığında oluşturulan uluslararası hukuk belgelerinde temsile bağlanan sonuçlar ulusal hukuk sistemleri ile karşılaştırmalı olarak incelenmiştir. Değişik hukuk sistemlerinde öngörülen düzenlemelerin karşılaştırmalı olarak ele alınması, sorunları en etkili şekilde çözecek kuralların oluşturulmasına katkı sunmaktadır. Bu hedefe ulaşmak amacıyla hukuk sistemimiz dışında İsviçre, Alman, Hollanda ve İngiliz hukukunda temsil kurumuna ilişkin yaklaşımlar araştırılmıştır. Çalışmamızda ulusal hukuk düzenlerine etki etme kabiliyeti olan uluslararası hukuk belgeleri de incelenmiştir. Bu kapsamda civil law ile common law geleneğinin temsil kavramına yansıması dikkate alınmıştır. Birinci bölümde Avrupa Birliği bünyesinde yürütülen faaliyetler sonucunda hazırlanan Avrupa Sözleşme Hukuku İlkeleri ve Avrupa Özel Hukuku’nun İlkeleri, Tanımları ve Model Kuralları işlenmiştir. Özel Hukukun Birleştirilmesi için Uluslararası Enstitü’nün çalışmaları ışığında oluşturulan Uluslararası Ticari Sözleşmelere İlişkin İlkeler ile Uluslararası Mal Satımlarında Temsile İlişkin Kovansiyon da çalışmamızın parçasını teşkil etmiştir. İkinci bölümde temsilin türleri mercek altına alınmıştır. Bu kapsamda doğrudan ve dolaylı temsil ile açık ve gizli temsil ayırımı irdelenmiştir. Kıta Avrupa hukuk sistemlerinde temsilcinin kendi adına veya başkası adına hareket etmesinde keskin bir ayırımın yapıldığı, ancak bu sert ayırımın tutarlı bir şekilde korunamadığı tespit edilmiştir. Dolaylı temsili gerçek bir temsil olgusu olarak tanımayan geniş bir yazımın olduğu, bu temsil türünün hukuk sistemlerinde genel olarak positif bir düzenlemeye kavuşturulmadığı belirlenmiştir. Ancak bir kimsenin kendi adına işlem yaptığı hallerde de hesabına işlem yapılana yönelik önemli hukuki sonuçların doğduğu sonucuna varılmıştır. Borçlar Kanununun temel sistematiği doğrudan ve dolaylı temsil ayırımına yer vermemiştir. Ancak kanunda dağınık bir şekilde yer alan normların dolaylı temsili düzenleyen genel nitelikte düzenlemeler olduğu görülmüştür. Dolaylı temsilin genel hükümlerde doğrudan temsilin yanında detaylı olarak hüküm altına alınması tavsiye edilmiştir. Üçüncü bölümde temsilin etkinlik kaynakları ve kapsamı üzerinde durulmuştur. Temsil yetkisi ile temel ilişki arasında kendine özgü bir bağın olduğu görülmüştür. Böylece temsil kurumu bir yandan sözleşmesel ilişkiyi, diğer yandan yetki verilişini kapsayan bir madalyonun iki yüzünü teşkil etmektedir. Dış temsil yetkisinin dayanağını teşkil eden BK. m. 41 f. 2’nin ve BK. m. 42 f. 3’ün belirsiz bir görünüm sergilediği tespit edilmiştir. Bu anlamda işlem hayatını etkin bir şekilde koruyan Alman MK. m. 170-173 hükümlerine benzer genel düzenlemelerin oluşturulması önerilmiştir. Dördüncü bölümde menfaat çatışması ve alt temsil kavramları işlenmiştir. Hukuk sistemimizde menfaat çatışmasına ilişkin genel bir hüküm bulunmamaktadır. Bu konudaki belirsizliğin giderilmesi için uluslararası belgelerde öngörülen kurallar ışığında doğrudan ve dolaylı temsili içerecek tarzda bir düzenlemenin benimsenmesi tavsiye edilmiştir. Alt temsil ile ilgili sorunların çözümünde ise BK. m. 83’ün ve BK. m. 506 f. 1’in gözetilmesi gerektiği tespit edilmiştir. Beşinci bölümde yetkisiz temsil kavramı ile temsil yetkisinin sona ermesi incelenmiştir. Hukuk sistemimiz yetkisiz yapılan sözleşmenin geleceği konusundaki takdir olanağını BK. m. 46’da öngörülen süre tayini dışında sadece temsil olunana tanımıştır. Üçüncü kişiye yetkisiz işlemden cayma hakkının verilmemesinin, önemli bir eksiklik olduğu tespit edilmiştir. Onamanın doğrudan ve dolaylı temsilde farklı etkiler meydana getirdiği sonucuna varılmıştır. Türk Borçlar Kanunu yetkisiz temsilcinin sorumluluğu konusunda esnek bir rejim benimsemiştir. Tarafların haklı menfaatlerinin korunmasına hizmet eden bu çözüm şekli desteklenmiştir. Üçüncü kişinin kötüniyeti, BK. m. 47’de öngörülen sorumluluğu tamamen kaldırmaktadır. Bu konudaki tartışmaların ortadan kaldırılması amacıyla, BK. m. 47 f. 1 c. 2’de yer alan kuralın her iki fıkrayı kapsayacak tarzda üçüncü fıkraya yerleştirilmesi önerilmiştir. Hukuk sistemimiz yetkinin sona ermesinde üçüncü kişiyi sınırlı koşullarda korumaktadır. Dış yetkinin varlığına güvenen iyiniyetli üçüncü kişiler bakımından korumanın genişletilmesi gerektiği savunulmuştur. Son bölümde temsilin etkisi incelenmiştir. Birinci kısımda doğrudan ve açık temsilcinin yaptığı işlemin, temsil olunan ve üçüncü kişi arasında doğrudan hukuki ilişkiler kurduğu neticesine ulaşılmıştır. Bölümün ikinci kısmında ise dolaylı ve gizli temsilde üçüncü kişi ile temsilci arasında kurulan sözleşmeye temsil olunanın ekonomik ve hukuki katılımının hangi ölçüde dikkate alındığı irdelenmiştir. Bu temsil türünde temsil olunan ile üçüncü kişi arasında doğrudan ilişki kurulmasına olanak tanıyan sistemlerde tarafların haklı menfaatlerinin korunması amacıyla öngörülen tedbirler tartışılmıştır.

Nowadays, the concept of limited effectiveness has undergone radical changes with the parties involved in the establishment of contracts. The rapid change that the transaction life has undergone has made the pretension of representation a mandatory phenomenon. Accordingly, the pretension of representation has become a subject to important stipulations in many international law documents, mainly in the national law systems. The uncertainty of the provisions regarding representation stipulated in our law system and that the parties do not protect their interests in a balanced manner have created the need for reassessment of the rules in this matter. The results linked to the representation in the international law documents created in the light of the harmonization activities in our study have been examined comparatively with the national law systems. The fact that the regulations stipulated in various law systems are dealt with comparatively provides contribution to the establishment of the rules that will resolve the problems in the most effective manner. For the purpose of achieving this objective, the approaches regarding the pretension of representation in the Swiss, German, Dutch and English laws apart from our law system have been researched. In our study, also the international law documents that have the capability of affecting the national law orders have been examined. Within this scope, the reflection of the tradition of civil law and common law to the representation concept has been taken into account. In the first section, the Principles of European Contract Law and the Principles, Definitions and Model Rules of European Private Law prepared as a result of the activities carried out within the body of European Union have been discussed. The Principles of International Commercial Contracts and the Convention on Agency in the International Sale of Goods established under the light of the studies of the International Institute for the Unification of Private Law have constituted a part of our study. In the second section, the types of the representation have been examined. Within this scope, the difference of the direct and indirect representation and the disclosed and undisclosed representation has been scrutinized. It has been found out that a sharp contrast is made in the act of representative in own name or in name of someone, but this harsh contrast cannot be maintained consistently in the Continental European law systems. It has been determined that there is a wide literature that does not recognize the indirect representation as an actual representation fact and that this representation type has not been provided with an positive regulation in general in the law systems. However, it has been concluded that also in cases where one person makes a transaction in own name, there occur significant legal results for the person on behalf of whom the transaction is made. The basic systematic in Code of Obligations does not include the contrast of direct and indirect representation. However, it has been observed that the norms dispersedly included in the law are general regulations that regulate the indirect representation. It has been recommended that the indirect representation is stipulated in detail as well as the direct representation in the general provisions. In the third section, the effectiveness resources and the scope of the representation have been discussed. It is observed that there is a specific correlation between authority and the basic relationship. In this way, the pretension of representation constitutes both sides of a coin that covers the contractual relationship on one side and the authorization on the other side. It has been found out that paragraph 2 of article 41 in Code of Obligations and paragraph 3 of article 42 in Code of Obligations constituting the basis of the power of external representation exhibit an uncertain appearance. In this sense, it has been recommended that the general regulations similar to the provisions of the articles 170-173 of the German Civil Law maintaining its transaction life in an effective manner are established. In the fourth section, the conflict of interest and the sub-representation concepts have been discussed. In our law system, there is no a general provision regarding the conflict of interest. In order to eliminate the uncertainty in this matter, it has been recommended that a regulation of the type to include the direct and indirect representation is adopted in the light of the rules stipulated in the international documents. It has been determined that in resolution of the problems related to the sub-representation, however, the article 83 in Code of Obligations and the paragraph 1 of the article 506 in Code of Obligations should be observed. In the fifth section, the cessation of the power of representation with the concept of the unauthorized representation has been examined. Our law system grants the estimation opportunity on the future of the contract entered into in an unauthorized manner only to the represented person except for the designation of period stipulated in article 46 in Code of Obligations. It has been determined that it is an important deficiency not to grant the right of withdrawal from the unauthorized transaction to the third person. It has been concluded that the approval causes different effects in the direct and indirect representation. Turkish Code of Obligations adopted a flexible regime about the responsibility of the unauthorized representative. This solution manner serving to the protection of the justified interests of the parties has been supported. The bad faith of the third person completely removes the responsibility stipulated in article 47 in Code of Obligations. For the purpose of eliminating the discussions on this matter, it has been recommended that the rule set forth in item 2 of paragraph 1 of article 47 in Code of Obligations is included into third paragraph so as to cover both paragraphs. Our law system protects the third person under limited conditions in termination of authority. It has been argued that the protection should be expanded in terms of the well-intentioned third persons relying on the presence of the external authority. In the final section, the effect of the representation has been examined. In the first part, it has been concluded that the transaction made by the direct and disclosed representative establishes direct legal relationships between the represented person and the third person. In the second part of the section, however, to which extent the economic and legal participation of the represented person in the contract made between the third person and the representative in the indirect and undisclosed representation is taken into consideration has been scrutinized. The measures required for the purpose of protecting the justified interests of the parties in the systems allowing for the establishment of direct relationship between the represented person and the third person in this representation type have been discussed.
Keywords: Alman; Avrupa; Avrupa Özel Hukuku’nun İlkeleri; Avrupa Sözleşme Hukuku İlkeleri; Borçlar hukuku; Civil law; Commercial contracts; Comparative Law; Comparison; Damage; Definitions and Model Rules of European Private Law; Direct representation; Doğrudan temsil; Dolaylı temsil; English; European; German; Hollanda; Hukuk; Indirect Representation; International law; İlkeler; İngiliz; İsviçre; Karşılaştırma; Karşılaştırmalı Hukuk; Law; Medeni hukuk; Netherlands; Obligations (Law); Özel hukuk; Power of attorney; Principles; Principles of European Contract Law; Principles of International Commercial Contracts; Private law; Switzerland; Tanımları ve Model Kuralları; Temsil yetkisi; Ticarî sözleşmeler; Uluslararası hukuk; Uluslararası Ticari Sözleşmelere İlişkin İlkeler; Unauthorized Representative; Yetkisiz Temsilci; Zarar